Legal Protection for Families in the Perspective of the Right to Non-Discrimination - Cynthia Hadita; Krisnaldo Triguswinri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The empirical problems of Wadas citizens who are suspected of receiving repressive actions from the state apparatus need to be studied in the perspective of the right to non-discrimination and analyzed using the conflict theory of Karl Marx. This study used the sociolegal research method by conducting direct interviews with Wadas residents who experienced the incident directly. The results of the study show that referring to Karl Marx's conflict theory, the role of conflict is in triggering social change and on the other hand legal protection is also needed for Wadas Citizens so that the right to non-discrimination against Wadas Citizens is not violated.